PENGARUH MEDIA SOSIAL INSTAGRAM TERHADAP PERUBAHAN PERILAKU KOMUNIKASI SECARA LANGSUNG PADA GENERASI Z DI JAKARTA SELATAN - Aulia Fadhilah Hana; Wulandari, Siti Hardiati; Hasan, Basri Made; Fantini, Endah (DISCOURSE: Indonesian Journal of Social Studies and Education, 2023)
The era of technology has given birth to conventional media, one of which is electronic media which plays an important role for humans in communicating through social media. This certainly results in the use of the internet and social media which continues to increase in Indonesia. One of the social media applications that is often used by Indonesians and is popular among Generation Z is the Instagram application. This research aims to see the influence between the use of Instagram on Generation Z's communication behavior by using a quantitative approach method, through distributing questionnaires to respondents through the Google Form feature. The population in this study were active users of the Instagram application as many as 100 respondents. The sample was drawn using the Slovin formula. The results showed that there is a significant influence between the use of Instagram on the communication behavior of Generation Z in South Jakarta both as a whole (simultaneously), and individually (partially).